ANALISIS KEPUTUSAN INVESTASI PADA SAHAM PERBANKAN MENGGUNAKAN CAPM DAN CAPM-MONTE CARLO - SILABAN, EMERALD DIORI; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 12 No 2 (2023), 2023)
This research purpose is to calculate value of beta and expected return on CAPM using historical data and using data from Monte Carlo simulations. The data used in this research is stock data from the infobank index15. The model used in this study is the CAPM equilibrium model and to estimate the stock price this research uses a Monte Carlo simulation. The results showed that beta calculations used historical data and simulated data on BBCA stocks (0,91578 and 0,89393), BBNI (2,10434 and 2,28636), BBRI (1,42862 and 1,43427), BMRI (1,28249 and 1,37485), and BBTN (2,49935 and 2,75265). With these results, BBCA stock is defensive because the beta is less than one and the other four stocks are aggressive because the beta is more than one. The expected return calculation results using historical data and simulation data are BBCA (5,42% and 5,28%), BBNI (6,46% and 8,05%), BBRI (5,87% and 6,36%), BMRI (5,74% and 6,24%), and BBTN (6,81% and 8,98%).